AN OVERVIEW OF DIRECTED READING ACTIVITY (DRA) AND READING COMPREHENSION - Edi Saputra (Getsempena English Education Journal, 2015)
This article describes about Directed Reading Activity (DRA) in teaching English, especially in reading comprehension. DRA is a strategy that provides students with instructional support before, during, and after reading process. Some principles of Directed Reading activity (DRA) strategy, including first, attention one of the principles of DRA that must be considered by the teacher to the learners when teaching reading in the classroom based on context to get meaning to develop skills and strategies in identifying words, sentences and paragraphs. Second, students have enough changes in reading a text deeply to identify main idea, specific/detail information, reference and also meaning in a text. Third, DRA encourages the learners to be skilled and have strategy, to explore the text aesthetically, particularly in relation to literature and to develop their conceptual prior knowledge by texts. And forth, DRA encourages the learners to self-monitoring when they are reading so that they can adjust their reading strategies as needed. It is chosen because it can create effective and creative readers who always use background knowledge to emphasize word recognition and comprehension in reading text by connecting what they are ready know and what they are reading. The learners are given chances to correct errors that occur during and after a reading process.